Characterization of Cauliflower OR Mutant Variants - Welsch, Ralf; Zhou, Xiangjun; Koschmieder, Julian; Schlossarek, Tim; Yuan, Hui; Sun, Tianhu; Li, Li (Frontiers in Plant Science, 2020)
Cauliflower Orange (Or) mutant is characterized by high levels of -carotene in its curd. Or mutation affects the OR protein that was shown to be involved in the posttranslational control of phytoene synthase (PSY), a major rate-limiting enzyme of carotenoid biosynthesis, and in maintaining PSY proteostasis with the plastid Clp protease system. A transposon integration into the cauliflower Or gene (BoOR) results in the formation of three differently spliced transcripts. One of them is characterized by insertion (BoOR-Ins), while the other two have exon-skipping deletions (BoOR-Del and BoOR-LD). We investigated the properties of individual BoOR variants and examined their effects on carotenoid accumulation. Using the yeast split-ubiquitin system, we showed that all variants were able to form OR dimers except BoOR-LD. The deletion in BoOR-LD eliminated the first of two adjacent transmembrane domains and was predicted to result in a misplacement of the zinc finger domain to the opposite side of membrane, thus preventing OR dimerization. As interaction with PSY is mediated by the N-terminus of BoOR, which remains unaffected after splicing, all BoOR variants including BoOR-LD maintained interactions with PSY. Overexpression of individual BoOR mutant variants in Arabidopsis revealed that their protein stability varied greatly. While overexpression of BoOR-Del and BoOR-Ins resulted in greatly increased BoOR protein levels, minimal amounts of BoOR-LD protein accumulated. Concomitantly, correlated carotenoid accumulation was observed in calli of Arabidopsis expressing these variants. Furthermore, we found that OR also functions in E. coli to increase the proportion of native, enzymatically active PSY from plants upon coexpression, but not of bacterial phytoene synthase CrtB. Taken together, these results suggest that OR dimerization is required for OR stability in planta and that the simultaneous presence of the N-terminal PSY interaction-domain is required for the holdase function of OR. The more pronounced effect of simultaneous expression of all BoOR variants in cauliflower Or mutant compared with individual overexpression on carotenoid accumulation suggests an enhanced activity with possible formation of BoOR heterodimers.